Laboratory Evaluation of Toxic and Repellent Properties of Dracaena arborea Against Sitophilus zeamais and Callosobruchus maculatus: Repellent Properties of Dracaena arborea on Grain Insects - Udo, Ime Okon (Biological Sciences - PJSIR, 2011)
Laboratory evaluation of ethanolic extract of Dracaena arborea leaves partitioned between equal volumes of chloroform, ethyl acetate, n-hexane and n-butanol to obtain various fractions was carried out to assess contact toxicity on filter paper and by topical application, toxicity of extracts applied on grains and repellent action against Sitophilus zeamais (Mots.) and Callosobruchus maculatus Fabricius on stored grains. Insects were exposed to both treated and untreated surfaces and mortality was scored at different times after treatment. Results obtained from the study showed the extract fractions causing significant mortality of both insects exposed to treatments. A contact toxicity of over 80% was recorded against zeamais from ethyl acetate fraction. Similarly, 100% mortality was recorded against C. maculatus from ethyl acetate fraction after 96 h of treatment. Results obtained from grain treatment produced a significant mortality of over 60% against C. maculatus from n-hexane fraction while the aqueous fraction significantly killed S. zeamais by over 15% compared with the control treatment. A strong repellent action was evoked against S. zeamais while moderate action was recorded against C. maculatus. An overall repellency of 40% and 24% was recorded from various extract fractions against S. zeamais and C. maculatus, respectively. The results obtained suggest a promising alternative to synthetic insecticides and the incorporation of arborea into storage pest management system is advised.